Factors associated with prolonged viral shedding in older patients infected with Omicron BA.2.2 - Zhong, Weijie; Yang, Xiaosheng; Jiang, Xiufeng; Duan, Zhixin; Wang, Wei; Sun, Zhaoliang; Chen, Wanghao; Zhang, Wenchuan; Xu, Jie; Cheng, Juan; Yuan, Xiaoling; Li, Yi (Frontiers in Public Health, 2023)
Background: To explore the risk factors associated with the viral shedding time in the elder Chinese patients infected with SARS-CoV-2 omicron. Methods: Participants infected with SARS-CoV-2 omicron were enrolled in a retrospective study, and divided into two groups according to the shedding time of omicron [≥10 days, "late clearance group" and < 10 days, "early clearance group"]. Results: 180 patients were enrolled in the study (88 early, 92 late), with a median time of viral shedding was 10 days and a mean age of 77.02 years. Prolonged SARS-CoV-2 omicron shedding was associated with old age (P=0.007), unvaccinated (P=0.001), delayed admission to hospital after illness onset (P =0.001), D-dimer (P=0.003) and methylprednisolone treatment (P=0.048). In the multivariable analysis, vaccinated [OR], 0.319 [95% CI, 0.130–0.786], P=0.013), paxlovid (OR, 0.259 [95% CI, 0.104–0.643], P=0.004), and time from onset to admission (OR, 1.802 [95% CI, 1.391–2.355], P=0.000) were significantly associated with viral clearance. Conclusions: The older age, methylprednisolone therapy, and D-dimer were associated with prolonged duration of omicron viral shedding. The time from onset to hospitalization, untreated with paxlovid and unvaccinated were independent risk factors in elder Chinese patients infected with SARS-CoV-2 omicron.